Manage your boss - Vehar, Johathan (Greensboro, NC : Center for Creative Leadership, 2016)
The relationship between you and your boss is important in determining your success at work.
WHAT IS "Managing Your Boss"?; WORKING ACROSS Boundaries; WHY IS Managing Your Boss Important?; THE PROBLEMS WITH Managing Your Boss; WHAT DOE SMY BOSS NEED TO DO in Order to Succeed?; STRATEGIES FOR Managing Your Boss; POINt Discussion Guide; CONCLUSION; BACKGROUND; SUGGESTED RESOURCES; ABOUT THE CENTER FOR CREATIVE LEADERSHIP.
Online resource; title from title page (Safari, viewed April 18, 2016).
Includes bibliographical references.
eBooks on EBSCOhost
Keywords: Supervisors; Employees; Interpersonal relations; Business communication; Agents de maîtrise.; Personnel; Communication dans l'entreprise.; supervisors; personnel; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Business communication; Employees; Interpersonal relations; Supervisors